1986
DOI: 10.1055/s-2008-1026881
|View full text |Cite
|
Sign up to set email alerts
|

Szintigraphische Diagnostik des Neuroblastoms mit meta-Jod-Benzylguanidin*

Abstract: In 1979/80 meta-iodobenzylguanidine (MIBG) was introduced as a radiopharmaceutical agent with high affinity to the adrenal medulla. It could be shown, that scintigraphic imaging with 131J labeled MIBG is a sensitive and highly specific method for localization of pheochromocytoma. In this connection we could demonstrate in 1983 that neuroblastoma can be visualized scintigraphically with MIBG as well. Until now 13 patients were examined with 131J-MIBG by our group: In 10 children with histologically proven neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…Several years ago it was shown that mIBG was a useful substance for scintigraphic imaging of neuroblastoma [14,15]. On this experience together with laboratory data showing good in vitro uptake and killing of tumor cells in human neuroblastoma cell lines [ 161 the first treatment study [4] expanded.…”
Section: Discussionmentioning
confidence: 99%
“…Several years ago it was shown that mIBG was a useful substance for scintigraphic imaging of neuroblastoma [14,15]. On this experience together with laboratory data showing good in vitro uptake and killing of tumor cells in human neuroblastoma cell lines [ 161 the first treatment study [4] expanded.…”
Section: Discussionmentioning
confidence: 99%
“…Thus l31I-MIBG uptake was observed in pheochromo cytoma [Shapiro et al, 1983;Fischer et al, 1982], neuroblastoma [Kimmig et al, 1983;Feine et al, 1984], métastasés of carcinoid tumors [Fischer et al, 1984] and in platelets [Feldman et al, 1984].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kimmig et al [1983] reported the imaging of neuro blastoma and Fischer et al [1984] scintigra phy of métastasés of carcinoid tumors with the same radiopharmaceutical agent.…”
mentioning
confidence: 99%
“…Das therapeutische Procedere ist vom exakten Staging und Therapiemonitoring abhängig. Dabei haben neben morphologisch orientierten bildgebenden Verfahren und der Bestimmung der Katecholaminmetabolite (Homovanillinsäure und Vanillinmandelsäure) in Serum und Urin (6) neben der Knochenszintigraphie seit der Einführung des Noradrenalin-Analogons Metaiodobenzylguanidin (mlBG, 21,22) nuklearmedizinischen Verfahren einen hohen Stellenwert (5,7,11).…”
Section: Nuklearmedizin 1996; 35: 220-4unclassified